Preparation method of high-performance copper-aluminum composite material
By pre -processing copper bands and using homemade AL base ingredients for high -quality welding in the cast and rolling process, the problem of unstable copper and aluminum composite row connection is solved, and the preparation of high -performance copper and aluminum composite materials has been realized. And conductive performance.
Patent Information
- Application Number
- CN202411738767.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-01-21
AI Technical Summary
The prior art is difficult to effectively connect the copper-aluminum composite row, resulting in unstable conductivity, and traditional welding methods have problems with unmelted zones and inclusion defects.
Under the assistance of pre -processing copper bands, and with the assistance of homemade powder AL base material, high -quality welding is performed by casting and rolling technology, using the melting rotation quenching method to prepare AlsiaG alloy sink, the ball is grinded into powder, and in a vacuum environment, it is performed in a vacuum environment. Laser spray pre -processing, complete the attachment of the pink powder, and finally obtain high -performance copper and aluminum composite materials through conventional casting technology.
The high-quality connection of the copper-aluminum composite row is achieved. The obtained welding joint has a uniform composition and no local weak areas. The grains in the welding area are fine and evenly distributed, which improves the tensile strength and mechanical properties of the copper-aluminum composite row.
Smart Images

Figure HDA0005162128540000011 
Figure HDA0005162128540000012 
Figure HDA0005162128540000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of processing copper-aluminum composite bars for electrical connection, and in particular relates to a method for preparing a high-performance copper-aluminum composite material. Background Art
[0002] my country's power and electrical technology is developing rapidly, especially driven by new energy vehicles, the use of high voltage and high current equipment is increasing. This has led to a significant increase in the demand for connection materials (such as busbars) between application equipment and power input, and at the same time, the requirements for its cost and energy-saving performance have become increasingly stringent. With the continuous advancement of industrial technology and the rapid development of the manufacturing industry, copper-aluminum composite plates and strips, as a high-performance composite material, are constantly expanding their application areas. From traditional electronics and electrical fields to emerging industries such as automobiles, energy, metallurgy, and machinery, the application of copper-aluminum composite plates and strips has gradually become popular and has become an indispensable and important material in modern industrial production.
[0003] At present, the commonly used busbars are copper and aluminum. Although copper has good conductivity, its cost is too high. At the same time, 75% of my country's copper raw materials need to be imported, and the cost will only be higher in the future, which limits the widespread application of pure copper. Although aluminum has a price advantage over copper, its conductivity is poor, especially in the connection parts. Since aluminum is very easy to oxidize, it will increase the contact resistance and the electrical performance will decline sharply. The copper-aluminum composite busbar is a material with aluminum as the base and copper as the outer layer. It can combine the high-quality and stable conductivity of copper with the low cost of aluminum, and combine it into a new type of conductor material with low contact resistance.
[0004] As a new type of composite material, copper-aluminum composite plate is widely used in various fields such as electronics, electrical appliances, electricity, metallurgical equipment, machinery, automobiles, energy and daily necessities. Market demand drives the rapid growth of the industry market size. According to statistics, the market size of my country's copper-aluminum composite plate and strip industry will be about 9.21 billion yuan in 2023, a year-on-year increase of 3.6%, and the average annual compound growth rate from 2016 to 2023 will reach about 22.2%.
[0005] Copper-aluminum composite materials are of great significance for reducing equipment costs and weight. At present, the preparation processes of copper-aluminum composite bars mainly include rolling composite method, explosion composite method and diffusion welding method. At present, the copper-aluminum composite materials produced in China are mainly prepared by explosion composite method, which has high cost, low efficiency and can only produce single plates. Composite copper-aluminum bars are also only in the stage of composite casting and hot penetration rolling, and the product quality is unstable, and there is a problem that aluminum oxidation cannot be solved. It is difficult to ensure excellent electrical or thermal conductivity by connecting copper-aluminum composite bars using traditional mechanical methods, and it is difficult to meet the use requirements. It is an effective method to obtain copper-aluminum composite bars by welding. At present, the methods of welding aluminum and copper include melting welding, solid welding and semi-solid welding. When aluminum and copper are melted and welded, the melting points of the two are quite different. The melting point of aluminum is much higher than that of copper, which is easy to produce unmelted areas and inclusion defects between the bonding layers; solid welding usually requires a large pressure and may be limited by the form of the pressure head; and semi-solid welding is trapped by the lack of a solder with ideal melting point and wettability. The preparation of dissimilar metal welding joints of copper-aluminum composite bars through metallurgical reaction between aluminum and copper has become a major technical barrier to industrial application.
[0006] At present, there are also relevant patent literature reports on the preparation process of copper-aluminum composite bars. For example: 1. The invention patent application CN202210608581.1 discloses a method for preparing a copper-aluminum composite material, which prepares nano-copper-nano-aluminum double-layer coated aluminum cluster particles, sintering the nano-copper-nano-aluminum double-layer coated aluminum cluster particles to obtain homogenized nano-copper-nano-aluminum double-layer coated aluminum clusters, using the homogenized nano-copper-nano-aluminum double-layer coated aluminum clusters as raw materials to prepare aluminum liquid, using casting and rolling equipment, and using a solid-liquid composite method under pressure to prepare a copper-aluminum composite material. 2. The invention patent CN 201510154095.7 discloses a copper-aluminum composite material and a preparation method thereof. The copper-aluminum composite material of the invention is produced by arc spraying with a spraying voltage of 30-35V, a spraying distance of 100-150mm, a wire feeding speed of 3-4m / min, a current of 120-150A, a compressed gas pressure of 0.65-0.75MPa, and a compressed gas flow rate of 1.6-2.0m3 / min. Copper is sprayed on the surface of an aluminum alloy substrate in an inert gas protective atmosphere to form a copper coating. The copper coating sprayed on the surface of the aluminum alloy substrate is not oxidized, is uniform and dense, is bright purple-red, has a high bonding strength with the substrate, and has good conductivity. It can be used for the preparation of high-voltage electrical products. Summary of the invention
[0007] The technical problem to be solved by the present invention is: for copper-aluminum dissimilar metals that are difficult to be connected into plate-shaped copper-aluminum composite bars by traditional welding methods, in order to overcome the technical problems existing in existing materials and technologies, the present invention provides a method for preparing a copper-aluminum composite layered plate with high interface bonding strength, less harmful phases, and can be used for industrial production, that is, the present invention provides a method for preparing a high-performance copper-aluminum composite material. The technical solution of the present invention adopts a pretreated copper strip, and completes high-quality welding of the copper strip and aluminum liquid in the casting and rolling process with the assistance of a homemade powdered Al-based solder; the pretreated copper strip shows higher atomic activity, which is conducive to atomic diffusion between copper and aluminum, and the homemade Al-based solder powder can inhibit the formation of metal compounds at the interface through high entropy of the interface to obtain a copper-aluminum composite material with excellent comprehensive performance.
[0008] In order to solve the above problems, the technical solution adopted by the present invention is:
[0009] The invention provides an Al-based solder, which is expressed in mass percentage and is prepared from raw materials of Al 75-85%, Si 10-15% and Ag 0.1-10% by melt spinning quenching method.
[0010] According to the above-mentioned Al-based solder, the preparation method of the Al-based solder is:
[0011] a. First, the selected metal elements are polished (to remove the surface oxide scale and ensure the purity of the raw materials). After polishing, various elements are weighed according to the ratio of the above-mentioned brazing material, and the weighed Al, Si and Ag are melted in an arc melting furnace. After melting, they are cooled to obtain an AlSiAg alloy ingot with uniform composition;
[0012] b. Cut the AlSiAg alloy ingot obtained in step a into small alloy pieces, take the alloy pieces and place them in a quartz tube, put the quartz tube into a vacuum induction wire spinning furnace SS-0.02, adjust the quartz tube so that the distance between the nozzle and the surface of the copper roller is 1.2-2 mm when it is in the injection position; then use a mechanical pump to pump low vacuum to 2.5 Pa, and a diffusion pump to pump high vacuum to 5.0×10 -2 Pa, fill with 0.06MPa pure argon as protective atmosphere, adjust the injection pressure to 0.02-0.03MPa, adjust the copper wheel speed to 3000-4000rpm, adjust the induction coil current to heat and melt the alloy, and spray the alloy melt onto the surface of the copper wheel under the action of the injection pressure, and rapidly cool it to obtain a (continuous, tough and surface quality) amorphous alloy thin strip;
[0013] c. Grind the amorphous alloy ribbon obtained in step b into powder to obtain powdered Al-based solder.
[0014] According to the Al-based solder, during the smelting process described in step a, the arc melting furnace is successively evacuated to a low vacuum of 2.5 Pa using a mechanical pump and to a vacuum of 5×10 -3 Pa, fill with 0.05MPa, 99.999% purity argon as a protective atmosphere, adjust the current to 50A, first strike an arc on the Ti ball, melt the Ti ball for 2 to 3 minutes to absorb oxygen, then adjust the current to 100-150A, use arc heating to melt the alloy 4 to 5 times, each melting time is 5 to 6min (the material is turned over during the melting process).
[0015] According to the above-mentioned Al-based solder, the outlet shape of the quartz tube in step b is a long strip, with an outlet width of 1.5 to 2 mm and a length of 1.5 to 10 mm.
[0016] According to the above-mentioned Al-based solder, the amorphous alloy ribbon obtained in step b has a thickness of 20 to 45 μm and a width of 2 to 20 mm (the alloy ribbon has a smooth surface, a flat edge and excellent toughness).
[0017] According to the above-mentioned Al-based solder, the specific process of ball-milling the amorphous alloy ribbon into powder in step c is as follows:
[0018] First, the obtained amorphous alloy ribbon is placed in an agate ball mill (in order to avoid crystallization of the amorphous alloy at high temperature), and anhydrous ethanol is added to the ball mill at a mass ratio of 1:1 to the amorphous alloy ribbon;
[0019] Then, the ball milling was performed, the ball-to-material ratio was controlled to be 10:1, the speed of the ball mill was 800 rpm, and the ball milling was performed for 12 hours to obtain a mixture of crushed solder powder and anhydrous ethanol;
[0020] Finally, the obtained solder powder and anhydrous ethanol mixture were placed in an oven for drying at a temperature of 65° C. for 6 h, and powdered Al-based solder was obtained after drying.
[0021] In addition, a method for preparing a high-performance copper-aluminum composite material is provided, the preparation method comprising the following steps:
[0022] 1) First, unfold the copper strip and clean the surface of the copper strip with industrial alcohol;
[0023] 2) Then, the powdered Al-based solder is sprayed onto the surface of the cleaned copper strip using an electrostatic spraying machine, and the surface to which the powdered Al-based solder is attached is treated using a laser shot peening machine;
[0024] 3) Finally, conventional casting and rolling technology is used to complete the semi-solid composite between the copper strip attached with the powdered Al-based solder and the aluminum liquid to obtain a copper-aluminum composite billet cast-rolled coil, that is, a high-performance copper-aluminum composite material.
[0025] The technical solution of the present invention is to use the pretreated copper strip to complete high-quality welding between the copper strip and the aluminum liquid in the casting and rolling process with the assistance of a homemade powdered Al-based solder. Specifically, the AlSiAg alloy thin strip material is prepared by a melt spinning method, and then the thin strip material is crushed into powder by a ball mill. After that, the surface of the copper strip is pretreated by laser shot peening in a vacuum environment to complete the attachment of the solder powder, and finally a high-performance copper-aluminum composite material is obtained by conventional casting and rolling technology.
[0026] The positive beneficial effects of the present invention are:
[0027] 1. Compared with the conventional brazing materials such as Al-Zn based brazing materials for existing metal brazing, the brazing materials prepared by the present invention have uniform element distribution inside, fine grains in the composite interface layer, no component segregation, and uniform melting and fast spreading speed, large wetting area and good wettability during the melting process, which is beneficial to industrial production (see attached for details). Figure 5 , 6 ); and the melt spinning quenching can directly obtain a thin strip of filler solder, eliminating the repeated rolling and annealing procedures in the preparation process, and the thin strip solder can be cut into any shape at will, reducing the manufacturing cost.
[0028] 2. The technical solution of the present invention, with the assistance of the self-made AlSiAg alloy solder, utilizes the capillary diffusion of the molten solder and the inhibitory effect of the harmful phase to complete the copper-aluminum interface bonding during the casting and rolling process. The obtained weld joint has uniform composition, no local weak area, and fine and uniformly distributed grains in the weld area (see Figure 7 Scanning image of the Cu side after welding with the new Al12Si8Ag solder. The new Al12Si8Ag solder diffuses in the Cu side base material and forms an Al-Cu intermetallic compound transition layer. The Cu side interface has good bonding. When powered on, it contains more grain boundaries and has higher interface energy, making the copper-aluminum composite bar have high tensile strength and excellent mechanical properties.
[0029] 3. The present invention uses Al, Si and Ag as alloy solder for copper-aluminum composite bars, which brings the following effects: first, it can reduce the eutectic temperature of the alloy solder; second, it can refine the interface grains of the composite bar; third, it can improve the wettability of the solder and the fluidity after melting; fourth, it can inhibit the growth of harmful phases in the interface layer; fifth, it can improve the mechanical properties, oxidation resistance and corrosion resistance of the brazed joint. Fig.10 The peel strength of the copper-aluminum composite material prepared by the new Al10Si5Ag brazing filler metal is determined by Fig.10It can be seen that after brazing with the new brazing filler metal, the peel strength of the copper-aluminum composite plate is as high as 160kN / m, with high peel strength, excellent mechanical properties, and reduced fracture toughness. Among them, Ag can increase the fluidity and ductility of the brazing filler metal in the molten state and increase the degree of wetting on the Cu matrix; Al-Si eutectic can significantly reduce the melting point of the aluminum-based brazing filler metal, can effectively remove the oxide film on the surface of the aluminum alloy, and its activity can protect the aluminum-based alloy; Si can hinder the formation of intermetallic compounds between aluminum and copper, refine the grains, and improve the quality of the weld joint.
[0030] 4. The present invention adopts the melt spinning method to prepare the solder, which has the following effects: first, the solder composition can be uniform without element segregation; second, thin strip or sheet solder can be obtained, which can be cut into various shapes to meet the welding requirements of special-shaped parts; third, the rolling, annealing and other processes are eliminated, thereby reducing production costs.
[0031] 5. The AlSiAg solder of the present invention has uniform element distribution without component segregation and element agglomeration due to its component design and melt spinning quenching technology; the solder powder obtained according to the solder base material composition and preparation method of the present invention is mostly in the form of flakes (such as Figure 4 As shown in the electron microscope scanning image of the prepared flaky solder powder, the size of the flaky solder powder is 20-80 μm) and is uniform in size, which is conducive to the attachment of the copper strip.
[0032] 6. The alloy solder prepared by the present invention, based on its unique composition design and atomic state, combined with the laser shot peening adhesion technology adopted by the present invention, can form a good connection between copper and aluminum. Under the premise of ensuring electrical properties, the formation of harmful phases on the copper-aluminum interface is inhibited, thereby improving the reliability of interface bonding.
[0033] 7. Comparison of relevant performance test data of existing copper-aluminum composite materials and the copper-aluminum composite materials prepared by the present invention using homemade powder solder (see Table 1 and Table 2 for details).
[0034] Table 1. Test data of relevant properties of existing copper-aluminum composite materials
[0035] serial number Existing copper-aluminum composite materials Serial number 1 Test date 2024 / 8 / 1 Stripping length (mm) 99 Sample length (mm) 200 Sample width (mm) 20 Average peel force (N) 983.14 Average peel strength (KN / m) 49.16 Minimum average peel force (N) 1001.67 Minimum peel strength (KN / m) 49.08 Maximum average peel force (N) 1015.74 Maximum peel strength (KN / m) 50.79
[0036] Table 2 Relevant performance test data of the copper-aluminum composite material prepared by the present invention
[0037] serial number Copper-aluminum composite material of the present invention Serial number 2 Test date 2024 / 9 / 28 Stripping length (mm) 175.2 Sample length (mm) 220 Sample width (mm) 20 Average peel force (N) 1310.88 Average peel strength (KN / m) 65.54 Minimum average peel force (N) 1302.72 Minimum peel strength (KN / m) 65.14 Maximum average peel force (N) 1325.53 Maximum peel strength (KN / m) 66.28
[0038] From the comparison of the data in Table 1 and Table 2, it can be seen that compared with the existing traditional solid-liquid composite cast-rolled copper-aluminum composite plate, the copper-aluminum composite plate obtained by brazing with the homemade new brazing filler metal in the present invention has a peeling force increased by 330N, and the average peeling strength increased by 16.38kN / m, and has more excellent mechanical properties. The copper-aluminum composite plate prepared with the new brazing filler metal will have a wider application field. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a macroscopic scanning morphology of the traditional solid-liquid composite cast-rolled copper-aluminum composite plate;
[0040] Depend on Figure 1 It can be seen that no obvious cracks were observed at the interface, the interface bonding layer was small, the copper-aluminum diffusion was not sufficient, and the joint strength was not high.
[0041] Figure 2 It is the peeling force curve of the composite sheet obtained by the conventional solid-liquid composite casting and rolling state;
[0042] Depend on Figure 2 It can be seen that when the peeling force is 714N, the composite plate breaks, and when the peeling force is 1142N, the composite plate is further peeled off, and two different peeling forces appear, indicating that the interface bonding of the traditional cast-rolled composite plate is uneven, and the stress concentration in the local weak strength area leads to microcracks, which eventually causes the peeling of the composite plate.
[0043] Figure 3 The peeling force curve of the copper-aluminum composite plate brazed by using the novel brazing filler metal prepared in Example 1 of the present invention;
[0044] Depend on Figure 3 It can be seen that the peeling force that causes the composite plate to fail is as high as over 1300N, which is 150N higher than that of the traditional cast-rolled composite plate. Not only has the peeling force been improved, but the composite plate welded with the new solder only has a small floating peeling force, indicating that the interface structure of this composite plate is more uniform.
[0045] Figure 4 This is an electron microscope scanning image of the flaky solder powder prepared in Example 1 of the present invention;
[0046] Depend on Figure 4 It can be seen that the size of the flake solder powder is 20-80 μm, and from the electron microscope scanning image, it is found that the size of the flake solder is relatively uniform.
[0047] Figure 5 This is an electron microscope scanning image of the interface of a copper-aluminum composite plate welded using the flaky solder powder prepared in Example 1;
[0048] Depend on Figure 5It was observed that a thick transition layer was formed at the copper-aluminum joint, and the solder diffused fully and evenly in the Cu / Al base material without obvious microcracks, indicating that the copper-aluminum composite plate welded using the flaky solder powder prepared in Example 1 of the present invention had a good bond.
[0049] Figure 6 This is a scanned image of a Cu / Al joint welded with the powder solder prepared in Example 3;
[0050] Depend on Figure 6 It was observed that a thicker transition layer was formed at the copper-aluminum joint, the solder diffused fully and evenly in the Cu / Al base material, and the solder diffused thicker on the Al side, indicating that the solder had good wettability on the Al base material, and no obvious microcracks were found at the joint, indicating that the flaky solder powder prepared in Example 3 of the present invention had a good bond with the copper-aluminum composite plate welded.
[0051] Figure 7 This is a scanning image of the Cu side after welding using the powder solder prepared in Example 3;
[0052] Depend on Figure 7 It can be seen that the new solder prepared in Example 3 of the present invention diffuses in the Cu-side base material and forms an Al-Cu intermetallic compound transition layer, and the Cu-side interface is well bonded.
[0053] Figure 8 This is a scanned image of a Cu / Al joint welded using the novel powder solder prepared in Example 5;
[0054] Depend on Figure 8 It can be seen that the interface grain size of the Cu / Al joint after welding with the novel solder prepared in Example 5 of the present invention is small, the structure is uniform, and no obvious microcracks are observed, indicating good bonding.
[0055] Fig. 9 This is a scanning image of the Cu side after welding using the new powder solder prepared in Example 5;
[0056] Depend on Fig. 9 It can be seen that the new solder prepared in Example 5 of the present invention diffuses fully in the Cu-side base material and forms an Al-Cu intermetallic compound transition layer, and the Cu-side interface is well bonded.
[0057] Fig.10 This is a graph of the peel strength of the copper-aluminum composite material prepared using the new powder solder prepared in Example 5;
[0058] Depend on Fig.10 It can be seen that after brazing with the new brazing filler metal, the peel strength of the copper-aluminum composite plate is as high as 160 kN / m, with high peel strength and excellent mechanical properties. DETAILED DESCRIPTION
[0059] The present invention is further described below in conjunction with embodiments, but the protection scope of the technical solution of the present invention is not limited thereto.
[0060] Embodiment 1:
[0061] The Al-based solder of the present invention is expressed in terms of mass percentage. The Al-based solder is prepared from raw materials of 85% Al, 14.9% Si and 0.1% Ag by using a melt spinning method.
[0062] The preparation method of the Al-based solder powder of the present invention comprises the following detailed steps:
[0063] a. First, select 99% Al, 99.99% Si and 99.99% Ag as raw materials, grind them with grinding wheels (remove the surface oxide scale to ensure the purity of the raw materials), weigh various metal elements and titanium balls according to the proportion of the above brazing materials, put the weighed Al, Si and Ag into a vacuum arc melting furnace, and use a mechanical pump to pump low vacuum to 2.5Pa, and a diffusion pump to pump vacuum to a vacuum degree of 5×10 -2 Pa; placing the electrode rod 1 cm above the titanium ball, filling with 0.05MPa, 99.999% pure argon as a protective atmosphere, adjusting the current to 50A, first striking an arc on the Ti ball, melting the Ti ball for 3 minutes to absorb oxygen, then adjusting the current to 150A, using arc heating to melt the alloy 5 times, each melting time is 5min (turning the material during the melting process); when the alloy ingot melts into an oblate spherical shape, the melting is completed; cooling after melting to obtain an AlSiAg alloy ingot with uniform composition;
[0064] b. Remove the oxide scale of the AlSiAg alloy ingot obtained in step a by using a grinding wheel, and then cut it into small alloy pieces of about 4-5g, take the alloy pieces and place them in a quartz tube (the outlet shape of the quartz tube is a long strip, the outlet width is 1.5-2mm, and the length is 1.5-10mm), put the quartz tube into a vacuum induction wire spinning furnace SS-0.02, adjust the quartz tube so that the distance between the nozzle and the surface of the copper roller is 1.2-2mm when it is in the injection position; then use a mechanical pump to pump low vacuum to 2.5Pa, and a diffusion pump to pump high vacuum to 5.0×10 -2 Pa, fill with 0.06MPa pure argon as protective atmosphere, adjust the injection pressure to 0.02-0.03MPa, adjust the copper wheel speed to 3000-4000rpm, adjust the induction coil current to 4-5A to heat and melt the alloy, spray the alloy melt onto the surface of the copper wheel under the action of the injection pressure, and rapidly cool it to obtain a 20mm wide and 30μm thick amorphous alloy ribbon (continuous, with excellent toughness and surface quality);
[0065] c. grinding the alloy strip obtained in step b into powder to obtain powdered Al-based solder;
[0066] The specific process of ball-milling amorphous alloy ribbon into powder is as follows:
[0067] First, the obtained amorphous alloy ribbon is placed in an agate ball mill (in order to avoid crystallization of the amorphous alloy at high temperature), and anhydrous ethanol is added to the ball mill at a mass ratio of 1:1 to the amorphous alloy ribbon;
[0068] Then, the ball milling was performed, the ball-to-material ratio was controlled to be 10:1, the speed of the ball mill was 800 rpm, and the ball milling was performed for 12 hours to obtain a mixture of crushed solder powder and anhydrous ethanol;
[0069] Finally, the obtained solder powder and anhydrous ethanol mixture were placed in an oven for drying at a temperature of 65° C. for 6 h, and powdered Al-based solder was obtained after drying.
[0070] Embodiment 2:
[0071] The present invention uses the powdered Al-based solder prepared in Example 1 to prepare a high-performance copper-aluminum composite material, and the detailed steps are as follows:
[0072] 1) First, unfold the copper strip and clean the surface of the copper strip with industrial alcohol;
[0073] 2) Then, an electrostatic spraying machine is used to spray powdered Al-based solder onto the surface of the cleaned copper strip, and a laser shot peening machine is used to treat the surface to which the powdered Al-based solder is attached;
[0074] 3) Finally, the conventional casting and rolling technology is used to complete the semi-solid composite between the copper strip with the powdered Al-based solder and the aluminum liquid to obtain a copper-aluminum composite billet casting roll, that is, a high-performance copper-aluminum composite material (the electron microscope scanning image of the obtained high-performance copper-aluminum composite material is shown in the attached Figure 5 ).
[0075] Figure 5 This is an electron microscope scanning image of the interface of the copper-aluminum composite plate welded using the flaky solder powder prepared in Example 1. Figure 5 It was observed that a thick transition layer was formed at the copper-aluminum joint, and the solder diffused fully and evenly in the Cu / Al base material without obvious microcracks, indicating that the copper-aluminum composite plate welded using the flaky solder powder prepared in Example 1 of the present invention had a good bond.
[0076] Embodiment 3:
[0077] The Al-based solder of the present invention is expressed in terms of mass percentage. The Al-based solder is prepared from raw materials of 80% Al, 12% Si and 8% Ag by using a melt spinning method.
[0078] The preparation method of the Al-based solder powder of the present invention comprises the following detailed steps:
[0079] a. First, select 99% Al, 99.99% Si and 99.99% Ag as raw materials, grind them with grinding wheels (remove the surface oxide scale to ensure the purity of the raw materials), weigh various metal elements and titanium balls according to the proportion of the above brazing materials, put the weighed Al, Si and Ag into a vacuum arc melting furnace, and use a mechanical pump to pump low vacuum to 2.5Pa, and a diffusion pump to pump vacuum to a vacuum degree of 5×10 -2 Pa; placing the electrode rod 1 cm above the titanium ball, filling with 0.05MPa, 99.999% pure argon as a protective atmosphere, adjusting the current to 50A, first striking an arc on the Ti ball, melting the Ti ball for 3 minutes to absorb oxygen, then adjusting the current to 150A, using arc heating to melt the alloy 5 times, each melting time is 5min (turning the material during the melting process); when the alloy ingot melts into an oblate spherical shape, the melting is completed; cooling after melting to obtain an AlSiAg alloy ingot with uniform composition;
[0080] b. Remove the oxide scale of the AlSiAg alloy ingot obtained in step a by using a grinding wheel, and then cut it into small alloy pieces of about 4-5g, take the small alloy pieces and place them in a quartz tube (the outlet shape of the quartz tube is a long strip, the outlet width is 1.5-2mm, and the length is 1.5-10mm), put the quartz tube into a vacuum induction wire spinning furnace SS-0.02, adjust the quartz tube so that the distance between the nozzle and the surface of the copper roller is 1.2-2mm when it is in the injection position; then use a mechanical pump to pump low vacuum to 2.5Pa, and a diffusion pump to pump high vacuum to 5.0×10 -2 Pa, fill with 0.06MPa pure argon as protective atmosphere, adjust the injection pressure to 0.02-0.03MPa, adjust the copper wheel speed to 3000-4000rpm, adjust the induction coil current to 4-5A to heat and melt the alloy, spray the alloy melt onto the surface of the copper wheel under the action of the injection pressure, and rapidly cool it to obtain a 20mm wide and 30μm thick amorphous alloy ribbon (continuous, with excellent toughness and surface quality);
[0081] c. grinding the alloy strip obtained in step b into powder to obtain powdered Al-based solder;
[0082] The specific process of ball-milling amorphous alloy ribbon into powder is as follows:
[0083] First, the obtained amorphous alloy ribbon is placed in an agate ball mill (in order to avoid crystallization of the amorphous alloy at high temperature), and anhydrous ethanol is added to the ball mill at a mass ratio of 1:1 to the amorphous alloy ribbon;
[0084] Then, the ball milling was performed, the ball-to-material ratio was controlled to be 10:1, the speed of the ball mill was 800 rpm, and the ball milling was performed for 12 hours to obtain a mixture of crushed solder powder and anhydrous ethanol;
[0085] Finally, the obtained solder powder and anhydrous ethanol mixture were placed in an oven for drying at a temperature of 65° C. for 6 h, and powdered Al-based solder was obtained after drying.
[0086] Embodiment 4:
[0087] The present invention uses the powdered Al-based solder prepared in Example 3 to prepare a high-performance copper-aluminum composite material, and the detailed steps are as follows:
[0088] 1) First, unfold the copper strip and clean the surface of the copper strip with industrial alcohol;
[0089] 2) Then, an electrostatic spraying machine is used to spray powdered Al-based solder onto the surface of the cleaned copper strip, and a laser shot peening machine is used to treat the surface to which the powdered Al-based solder is attached;
[0090] 3) Finally, the conventional casting and rolling technology is used to complete the semi-solid composite between the copper strip with the powdered Al-based solder and the aluminum liquid to obtain a copper-aluminum composite billet casting roll, that is, a high-performance copper-aluminum composite material (the scanning image of the Cu / Al joint of the obtained high-performance copper-aluminum composite material is shown in the attached figure). Figure 6 , the Cu side scanning image after welding is shown in the attached Figure 7 ).
[0091] Depend on Figure 6 It was observed that a thick transition layer was formed at the copper-aluminum joint, the solder diffused fully and evenly in the Cu / Al base material, and the solder diffused thicker on the Al side, indicating that the solder prepared by the present invention had good wettability on the Al base material, and no obvious microcracks were found at the joint. Therefore, the flaky solder powder prepared in Example 3 of the present invention welded the copper-aluminum composite plate well.
[0092] Depend on Figure 7 It can be seen that the new solder prepared in Example 3 of the present invention diffuses in the Cu-side base material and forms an Al-Cu intermetallic compound transition layer, and the Cu-side interface is well bonded.
[0093] Embodiment 5:
[0094] The Al-based solder of the present invention is expressed in terms of mass percentage. The Al-based solder is prepared from raw materials of 85% Al, 10% Si and 5% Ag by using a melt spinning method.
[0095] The preparation method of the Al-based solder powder of the present invention comprises the following detailed steps:
[0096] a. First, select 99% Al, 99.99% Si and 99.99% Ag as raw materials, grind them with grinding wheels (remove the surface oxide scale to ensure the purity of the raw materials), weigh various metal elements and titanium balls according to the proportion of the above brazing materials, put the weighed Al, Si and Ag into a vacuum arc melting furnace, and use a mechanical pump to pump low vacuum to 2.5Pa, and a diffusion pump to pump vacuum to a vacuum degree of 5×10 -2 Pa; placing the electrode rod 1 cm above the titanium ball, filling with 0.05MPa, 99.999% pure argon as a protective atmosphere, adjusting the current to 50A, first striking an arc on the Ti ball, melting the Ti ball for 3 minutes to absorb oxygen, then adjusting the current to 150A, using arc heating to melt the alloy 5 times, each melting time is 5min (turning the material during the melting process); when the alloy ingot melts into an oblate spherical shape, the melting is completed; cooling after melting to obtain an AlSiAg alloy ingot with uniform composition;
[0097] b. Remove the oxide scale of the AlSiAg alloy ingot obtained in step a by using a grinding wheel, and then cut it into small alloy pieces of about 4-5g, take the small alloy pieces and put them in a quartz tube, put the quartz tube into a vacuum induction wire-spinning furnace SS-0.02 (the outlet shape of the quartz tube is a long strip, the outlet width is 1.5-2mm, and the length is 1.5-10mm), adjust the quartz tube so that the distance between the nozzle and the surface of the copper roller is 1.2-2mm when it is in the injection position; then use a mechanical pump to pump low vacuum to 2.5Pa, and a diffusion pump to pump high vacuum to 5.0×10 -2 Pa, fill with 0.06MPa pure argon as protective atmosphere, adjust the injection pressure to 0.02-0.03MPa, adjust the copper wheel speed to 3000-4000rpm, adjust the induction coil current to 4-5A to heat and melt the alloy, spray the alloy melt onto the surface of the copper wheel under the action of the injection pressure, and rapidly cool it to obtain a 20mm wide and 30μm thick amorphous alloy ribbon (continuous, with excellent toughness and surface quality);
[0098] c. grinding the alloy strip obtained in step b into powder to obtain powdered Al-based solder;
[0099] The specific process of ball-milling amorphous alloy ribbon into powder is as follows:
[0100] First, the obtained amorphous alloy ribbon is placed in an agate ball mill (in order to avoid crystallization of the amorphous alloy at high temperature), and anhydrous ethanol is added to the ball mill at a mass ratio of 1:1 to the amorphous alloy ribbon;
[0101] Then, the ball milling was performed, the ball-to-material ratio was controlled to be 10:1, the speed of the ball mill was 800 rpm, and the ball milling was performed for 12 hours to obtain a mixture of crushed solder powder and anhydrous ethanol;
[0102] Finally, the obtained solder powder and anhydrous ethanol mixture were placed in an oven for drying. The drying time was 6 hours and the drying temperature was 65° C. After drying, powdered Al-based solder was obtained.
[0103] Embodiment 6:
[0104] The present invention uses the powdered Al-based solder prepared in Example 5 to prepare a high-performance copper-aluminum composite material, and the detailed steps are as follows:
[0105] 1) First, unfold the copper strip and clean the surface of the copper strip with industrial alcohol;
[0106] 2) Then, an electrostatic spraying machine is used to spray powdered Al-based solder onto the surface of the cleaned copper strip, and a laser shot peening machine is used to treat the surface to which the powdered Al-based solder is attached;
[0107] 3) Finally, the conventional casting and rolling technology is used to complete the semi-solid composite between the copper strip with the powdered Al-based solder and the aluminum liquid to obtain a copper-aluminum composite billet casting roll, that is, a high-performance copper-aluminum composite material (the scanning image of the Cu / Al joint of the obtained high-performance copper-aluminum composite material is shown in the attached figure). Figure 8 , the Cu side scanning image after welding is shown in the attached Fig. 9 , the peel strength of high performance copper-aluminum composite materials is detailed in the attached Fig.10 ).
[0108] Depend on Figure 8 It can be seen that the interface grain size of the Cu / Al joint after welding using the new brazing filler metal prepared in Example 5 of the present invention is small, the structure is uniform, and no obvious microcracks are observed, indicating that the bonding is good. Fig. 9 It can be seen that the new solder prepared in Example 5 of the present invention diffuses fully in the Cu-side base material and forms an Al-Cu intermetallic compound transition layer, and the Cu-side interface is well bonded. Fig.10 It can be seen from the peel strength graph that after brazing using the new brazing filler metal prepared in Example 5 of the present invention, the peel strength of the copper-aluminum composite plate is as high as 160 kN / m, which has high peel strength and excellent mechanical properties.
Claims
1. An Al-based solder, characterized in that: Expressed in terms of mass percentage, the Al-based solder is prepared from raw materials of 75-85% Al, 10-15% Si and 0.1-10% Ag by melt spinning method.
2. The Al-based solder according to claim 1, characterized in that: The preparation method of the Al-based solder is: a. First, the selected metal elements are polished, and then various elements are weighed according to the proportion of the brazing material according to claim 1, and the weighed Al, Si and Ag are melted in an arc melting furnace, and cooled after melting to obtain an AlSiAg alloy ingot with uniform composition; b. Cut the AlSiAg alloy ingot obtained in step a into small alloy pieces, take the alloy pieces and place them in a quartz tube, put the quartz tube into a vacuum induction wire spinning furnace SS-0.02, adjust the quartz tube so that the distance between the nozzle and the surface of the copper roller is 1.2-2 mm when it is in the injection position; then use a mechanical pump to pump low vacuum to 2.5 Pa, and a diffusion pump to pump high vacuum to 5.0×10 -2 Pa, fill with 0.06MPa pure argon as a protective atmosphere, adjust the injection pressure to 0.02-0.03MPa, adjust the copper wheel speed to 3000-4000rpm, adjust the induction coil current to heat and melt the alloy, and spray the alloy melt onto the surface of the copper wheel under the action of the injection pressure, and rapidly cool it to obtain an amorphous alloy ribbon; c. Grind the amorphous alloy ribbon obtained in step b into powder to obtain powdered Al-based solder.
3. The Al-based solder according to claim 2, characterized in that: During the smelting process in step a, the arc melting furnace is successively evacuated to a low vacuum of 2.5 Pa using a mechanical pump and to a vacuum of 5×10 -3 Pa, fill in 0.05MPa, 99.999% purity argon as a protective atmosphere, adjust the current to 50A, first strike an arc on the Ti ball, melt the Ti ball for 2 to 3 minutes to absorb oxygen, then adjust the current to 100 to 150A, use arc heating to melt the alloy 4 to 5 times, and each melting time is 5 to 6 minutes.
4. The Al-based solder according to claim 2, characterized in that: In step b, the outlet shape of the quartz tube is a long strip, with an outlet width of 1.5 to 2 mm and a length of 1.5 to 10 mm.
5. The Al-based solder according to claim 2, characterized in that: The amorphous alloy ribbon obtained in step b has a thickness of 20 to 45 μm and a width of 2 to 20 mm.
6. The Al-based solder according to claim 2, characterized in that: The specific process of ball-milling the amorphous alloy ribbon into powder in step c is as follows: Firstly, the obtained amorphous alloy ribbon is placed in an agate ball mill, and anhydrous ethanol is added into the ball mill at a mass ratio of 1:1 to the amorphous alloy ribbon; Then, the ball milling was performed, the ball-to-material ratio was controlled to be 10:1, the speed of the ball mill was 800 rpm, and the ball milling was performed for 12 hours to obtain a mixture of crushed solder powder and anhydrous ethanol; Finally, the obtained solder powder and anhydrous ethanol mixture were placed in an oven for drying at a temperature of 65° C. for 6 h, and powdered Al-based solder was obtained after drying.
7. A method for preparing a high-performance copper-aluminum composite material, characterized in that: The preparation method comprises the following steps: 1) First, unfold the copper strip and clean the surface of the copper strip with industrial alcohol; 2) Then, an electrostatic spraying machine is used to spray the powdered Al-based solder prepared by claim 1 onto the surface of the cleaned copper strip, and a laser shot peening machine is used to treat the surface to which the powdered Al-based solder is attached; 3) Finally, conventional casting and rolling technology is used to complete the semi-solid composite between the copper strip attached with the powdered Al-based solder and the aluminum liquid to obtain a copper-aluminum composite billet cast-rolled coil, that is, a high-performance copper-aluminum composite material.
Citation Information
Patent Citations
A kind of copper-aluminum composite material and preparation method thereof
CN104805392B
Preparation method of copper-aluminum composite material
CN114951647A
Cited By
Copper-secondary aluminum compounding process with low cost and high utilization rate
CN121450978A
Laser-brazing-pressure multi-composite preparation method of dissimilar metal composite plate
CN121847965A
Method for laser-brazing-pressure multiple composite preparation of dissimilar metal composite plate
CN121847965B